The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1161/01.cir.70.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

The use of left ventricular end-ejection pressure and peak pressure in the estimation of the end-systolic pressure-volume relationship.

Abstract: The end-systolic pressure-volume relationship (ESPVR) as derived from left ventricular pressure-volume loops has gained increasing acceptance as an index of ventricular contractile function. In animal experiments the ESPVR has been defined as a line connecting the upper left corners of several differently loaded pressure-volume (P-V) loops with a slope parameter Ees and a volume axis intercept parameter V.. In the clinical setting, several variants of the ESPVR have been determined with use of peak left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(64 citation statements)
references
References 29 publications
3
61
0
Order By: Relevance
“…This motivated us to study the effect of MMR on ventricular contractility not only with the ϩdP/dt max approach but also in the pressure-volume plane. Several investigators have demonstrated that the ESPVR, as well as its slope (maximal ventricular elastance), E max , is relatively insensitive under physiological conditions to changes in preload and afterload yet sensitive to changes to the contractile state of the ventricle (5,10,11,15,16,40). In the present study, we observed that from rest to mild exercise, dP/dt max rose significantly, yet this rise was Ͻ5%.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This motivated us to study the effect of MMR on ventricular contractility not only with the ϩdP/dt max approach but also in the pressure-volume plane. Several investigators have demonstrated that the ESPVR, as well as its slope (maximal ventricular elastance), E max , is relatively insensitive under physiological conditions to changes in preload and afterload yet sensitive to changes to the contractile state of the ventricle (5,10,11,15,16,40). In the present study, we observed that from rest to mild exercise, dP/dt max rose significantly, yet this rise was Ͻ5%.…”
Section: Discussionsupporting
confidence: 45%
“…To overcome these limitations, LV contractility has been studied with the pressure-volume technique. The maximal elastance (E max ), measured as LV end-systolic pressure-volume relationship (ESPVR) obtained under different loading conditions, has been validated by several investigators as a model to evaluate LV contraction and is useful for quantifying inotropic state independent of preload and afterload under physiological conditions (7,10,11,15,17,40,41). Employing the pressure-volume analysis technique, we conducted this investigation in an effort to clarify how the MMR modifies LV contractility during mild and moderate dynamic exercise.…”
mentioning
confidence: 99%
“…Moreover, they also are influenced by changes in cardiac mass and morphology. It is widely accepted that the end-systolic pressure-volume relationship, as well as its slope, E max , are relatively insensitive under physiological conditions to changes in preload and afterload yet sensitive to changes to the contractile state of the ventricle (7,14,15,21,22,49). Since E max also is known to be susceptible to changes in chamber size (an increase in cardiac size-volume decreases E max regardless of contractility) (48), we also calculated PRSW [a modification of the Sarnoff's curve that represents the slope of the relationship between stroke work (SW ϭ pressure ϫ volume) and end-diastolic volume (EDV)].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular contractility was assessed by employing the slope of the line intersecting the end-systolic pressure-volume relationships (E max : maximal elastance index) and preload-recruitable stroke work index (PRSW) calculated from the stroke work-end-diastolic volume relationship. Both have been shown to be sensitive to changes in ventricular contractility and relatively insensitive to loading conditions, and the latter measure (PRSW) has been shown to be independent of changes in ventricular chamber size (9,14,15,21,23,49,50). We hypothesized that in the HF state, the muscle metaboreflex-induced increase in LV contractility during mild and moderate dynamic exercise would be impaired as shown by a smaller rise or no change in E max and PRSW.…”
mentioning
confidence: 99%
“…The E es and V 0 were calculated by an iterative linear regression method. 17,18 We excluded the first 5 beats to avoid the possible effects of changes in parallel conductance associated with alterations in right ventricular volume. …”
Section: Espvr Determination From Multiple P-v Loops (True E Es )mentioning
confidence: 99%